PENGARUH IKLAN DAN KEMUDAHAN TERHADAP KEPUTUSAN PENGGUNAAN APLIKASI OVO SERTA DAMPAKNYA TERHADAP IMPULSE BUYING - Ade Rahma; Ari Syahputra; Purba, Rakhmawati (Sekolah Tinggi Ilmu Ekonomi Bina karya, 2022)
The research aims to analyze the effect of advertising and convenience on mobile phone usage decisions and their impact on impulse buying (Case study of Ovo application users in Tebing Tinggi City). The research method used is quantitative with SPSS version 25.00. Data was collected from the results of distributing questionnaires to 96 respondents. Methods of data analysis in this study using test instruments, namely validity and reliability. The classic assumption test consists of normality, multicollinearity and heteroscedasticity. Linear regression analysis, coefficient of determination (R2) and hypothesis testing, namely the T test and path. Research results: advertising and convenience influence decisions, usage. Advertising has no effect on impulse buying. Convenience and usage decisions affect impulse buying. Advertising has no effect on impulse buying through usage decisions. Convenience does not affect impulse buying through the decision to use the OVO Application in Tebing Tinggi City. The decision variable for using is not intervening